Sentinel lymph node dissection in more than 1200 prostate cancer cases: Rate and prediction of lymph node involvement depending on preoperative tumor characteristics. (9th May 2013) - Winter, Alexander; Kneib, Thomas; Henke, Rolf‐Peter; Wawroschek, Friedhelm
<x xml:space="preserve">Abstract</x> Objectives To stratify the rate and prediction of lymph node involvement in prostate cancer patients undergoing sentinel‐lymphadenectomy depending on preoperative tumor characteristics, and to compare the outcome with the European Association of Urology Guideline indication for lymphadenectomy. Methods A total of 1229 patients (median age 66 years) were treated with open sentinel‐lymphadenectomy and prostatectomy between 2005 and 2009. Median preoperative prostate‐specific antigen was 7.4 ng/mL. The rate of lymph node involvement was analyzed for D'Amico risk groups. Multivariable logistic regression was used to estimate the probability of lymph node involvement. Predictor variables included preoperative prostate‐specific antigen, clinical T‐category and biopsy Gleason sum. Predictive accuracy has been quantified (area under the curve) and lymph node positive patients were verified under consideration of the recommended European threshold for lymphadenectomy (nomogram‐predicted lymph node invasion risk of >7%). Results The median number of lymph nodes removed was 10 (interquartile range 7–13). Overall, 17.1% of patients had lymph node involvement; 3.2% in low‐, 14.8% in intermediate‐ and 37.4% in high‐risk disease. The predicted risk for lymph node involvement ranged from 2% (prostate‐specific antigen ≤4 ng/mL, T1, Gleason sum ≤6) to 87% (prostate‐specific antigen >20 ng/mL, T3, Gleason sum ≥8). The predictive accuracy was 82.1%. According to the European guidelines, 15.9% of all lymph node involved cases would not have been detected. Conclusions The rate of lymph node involvement seems to be higher in the examined sentinel collective than expected according to the European Guideline nomogram. The first sentinel‐based lymph node involvement prediction model can assist in deciding on the indication for sentinel‐lymphadenectomy. The validation of a corresponding sentinel‐based nomogram is still missing.